Remote Thromboembolic Complications after Mitral Valve Replacement - K. V. Pukas (Ukrainian Journal of Cardiovascular Surgery, 2019)
The aim of this research was to investigate remote thromboembolic complications after mitral valve replacement. Analy-sis group included 634 patients with isolated mitral valve disease who were on treatment at the National M.M. Amosov Institute of Cardiovascular Surgery from 1 January, 2005, till 1 January, 2007. The mean duration of the follow-up was 9.3 ± 0.9 years. The main parameters studied within 10 years were survival (69.4%), stability of good and satisfactory results (57.3%), freedom from thromboembolic complications (79.7%), freedom from reoperations (95.4%). The study included 299 (47.1%) men and 335 (52.9%) women. The mean age of the subjects was 53.1 ± 8.5 years. 89 (34.1%) patients were classified in class II by NYHA, 199 (31.7%) in class III and 380 (60.0%) in class IV. The most common etiology of the dis-order was rheumatism combined with lipoidosis and myxomatosis (67.5%). The mean duration of rheumatic disease was 17.3 ± 4.9 years. The mean duration of atrial fibrillation was 3.1 ± 0.9 years.Mitral valve replacement (MVR) was carried out in all the subjects. The following types of bileaflet valve prostheses were used for mitral valve replacement: St. Jude, On-X, Carbomedics, Edwards MIRA. Based on the analysis, the risk factors of remote thromboembolic complications were revealed (type of the prosthesis, adequacy of anticoagulant therapy, occur-rence of prosthetic-dependent complications such as prosthetic endocarditis, panus or thrombosis of mitral valve prosthesis, increased left atrium size of more than 5.0 cm, contractility disorders). Mitral valve replacement is recommended for the patients of II–III class with sinus rhythm.After the mitral valve replacement, patients (especially those at risk: patients with long-term atrial fibrillation, rheumatic heart disease, atriomegaly) need permanent clinical supervision by cardiologist at the place of residence. In order to prevent and reduce the risk of thromboembolic complications, concomitant procedures are obligatory during mitral valve replace-ment: ligation of left atrium appendage, Cox Maze procedure, left atrium plasty and anticoagulant therapy escalation using an antiplatelet agent.